2007
DOI: 10.2190/r784-4504-37m3-2370
|View full text |Cite
|
Sign up to set email alerts
|

Learning through Ancient Art and Experiencing Emotions with Contemporary Art: Comparing Visits in Two Different Museums

Abstract: The aim of the present research was to explore possible differences between visitor experiences in two different kinds of art museums according to the art styles of the collections hosted: the Museum Borghese of Rome (ancient art) and the Peggy Guggenheim Collection of Venice (contemporary art). Two questionnaires were administered to 500 Italian participants before and after their visit to one of the museums. Questions (Likert scales and multiple choice) assessed how much visitors liked and were satisfied wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 8 publications
(16 reference statements)
2
24
0
Order By: Relevance
“…Previous studies have reported a difference between the two art styles in several psychological indicators. Modern art museum visitors were found to have higher scores on the Zuckerman (1979) "sensation seeking" personality trait, compared to visitors to ancient art museum, who focused on cultural enrichment (Mastandrea, Bartoli, & Bove, 2007, 2009). It may be that modern art visitors are challenged and aroused by their visit, whereas figurative art visitors are seeking a more contemplative experience.…”
Section: Art Museums As Restorative Environmentsmentioning
confidence: 98%
“…Previous studies have reported a difference between the two art styles in several psychological indicators. Modern art museum visitors were found to have higher scores on the Zuckerman (1979) "sensation seeking" personality trait, compared to visitors to ancient art museum, who focused on cultural enrichment (Mastandrea, Bartoli, & Bove, 2007, 2009). It may be that modern art visitors are challenged and aroused by their visit, whereas figurative art visitors are seeking a more contemplative experience.…”
Section: Art Museums As Restorative Environmentsmentioning
confidence: 98%
“…In hindsight, we acknowledge that our study was only conducted in one museum of modern art in central Europe and therefore has its limitations. The results also consider only museum visitors, not non‐museum visitors (other sociological studies dealing with museum experiences likewise do not analyze the experience of non‐visitors, for example Bourdieu and Darbel 1991; Mastandrea, Bartoli, and Bove ). That said, our interest is not to compare museum visitors with non‐visitors, but to understand various manners of experiencing exhibitions.…”
mentioning
confidence: 99%
“…Yet only a minority of about 10% of participants appeared to be vulnerable to this bias; a simple method to minimize this validity problem would be to measure the AAI outside an interview-like survey, for example, by anonymous self-declaration not in the presence of an observer. Second, similar to the studies of Bourdieu and Darbel (1991), Smith and Smith (2006), and Mastandrea et al. (2007), we gathered empirical data in museums, and no control group of non-museum visitors was included.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in several studies, the differentiation of artistically naïve and artistically experienced participants was based on small samples, which were not representative because they originated exclusively from university student populations. Only few studies included actual museum visitors (Bourdieu and Darbel, 1991; Mastandrea, Bartoli, & Bove, 2007; Smith & Smith, 2006).…”
mentioning
confidence: 99%